2006
DOI: 10.1002/jcb.21110
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of cyclooxygenase‐2 and inducible nitric oxide synthase by 4‐hydroxynonenal in human osteoarthritic chondrocytes through ATF‐2/CREB‐1 transactivation and concomitant inhibition of NF‐κB signaling cascade

Abstract: 4-hydroxynonenal (HNE), a lipid peroxidation end product, is produced abundantly in osteoarthritic (OA) articular tissues and was recently identified as a potent catabolic factor in OA cartilage. In this study, we provide additional evidence that HNE acts as an inflammatory mediator by elucidating the signaling cascades targeted in OA chondrocytes leading to cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) gene expression. HNE induced COX-2 protein and mRNA levels with accompanying increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 49 publications
4
50
0
Order By: Relevance
“…Since the induction of proinflammatory mediators by LPS is known to be predominantly regulated by NF-κB and AP-1 [27][30], we investigated if genkwanin exerts anti-inflammatory activities by affecting these two pathways. As shown in Figure 3, genkwanin significantly suppressed the AP-1 signaling pathway (Figure 3A) but had little effect on the NF-κB signaling pathway (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Since the induction of proinflammatory mediators by LPS is known to be predominantly regulated by NF-κB and AP-1 [27][30], we investigated if genkwanin exerts anti-inflammatory activities by affecting these two pathways. As shown in Figure 3, genkwanin significantly suppressed the AP-1 signaling pathway (Figure 3A) but had little effect on the NF-κB signaling pathway (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB plays a critical role in the onset of inflammatory responses and is involved in the transcriptional regulation of inflammatory mediators (Spooren et al, 2010;Vaillancourt et al, 2007). In resting cells, NF-κB and IκB-α are in a combined complex form in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Marsche et al [23] discovered that HDL treated with hypochlorous acid, a component of RCS, led to a reduction in eNOS expression in endothelial cells and, upon further investigation, found that 2-ClHDA was responsible for the reduction in eNOS. An abundant non-chlorinated lipid aldehyde, HNE, has been shown to induce COX-2 expression in RAW264.7 macrophages [34,35] and in human osteoarthritic chondrocytes [35]. In the present study, we show that TNF-a, 2-ClHDA, and 2-ClHA, but not 2-ClHOH, induce an increase in COX-2 Following COX-2 analysis, blots were subsequently stripped and then subjected to western blotting for b-actin, which was used to normalize each experimental analysis of COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%